2003
DOI: 10.1029/2002jd002613
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal radio frequency pulse distribution of intracloud‐lightning signals recorded by the FORTE satellite

Abstract: [1] The FORTE satellite's radio frequency receiver payload has made millions of recordings of lightning discharges. The most commonly occurring such radio emission arises from intracloud (IC) electrical breakdown and is usually recognizable by a pulse followed by a delayed echo from the ground reflection. We show that these IC pulses have two polar opposite types that together account for much of the pulse population. One type is a very bright pulse characterized by extended width (>2 ms), deep random fading w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 46 publications
(74 reference statements)
0
66
0
Order By: Relevance
“…8-11 of the present study confirm that at the high VHF TIPP ERP ranges, say >30 kW, the likelihood of prompt concurrence above the PDD threshold (top-of-cloud peak emission power ∼ 3×10 8 W) falls monotonically versus increasing ERP. We remark that since the earliest report of NBE sferics (Le Vine, 1980), all studies of this phenomenon have observed that NBE sferics are synchronously accompanied by the most intense VHF emissions of any lightning Jacobson and Light, 2003;Nag andRakov, 2009, 2010a, b;Nag et al, 2010;Smith, 1998;Thomas et al, 2001;Willett et al, 1989Willett et al, , 1990Willett and Krider, 2000). Thus, the results of Figs.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…8-11 of the present study confirm that at the high VHF TIPP ERP ranges, say >30 kW, the likelihood of prompt concurrence above the PDD threshold (top-of-cloud peak emission power ∼ 3×10 8 W) falls monotonically versus increasing ERP. We remark that since the earliest report of NBE sferics (Le Vine, 1980), all studies of this phenomenon have observed that NBE sferics are synchronously accompanied by the most intense VHF emissions of any lightning Jacobson and Light, 2003;Nag andRakov, 2009, 2010a, b;Nag et al, 2010;Smith, 1998;Thomas et al, 2001;Willett et al, 1989Willett et al, , 1990Willett and Krider, 2000). Thus, the results of Figs.…”
mentioning
confidence: 53%
“…Further observations on NBEs and their associated VHF TIPPs were presented in publications based on FORTE (Jacobson, 2003a, b;Jacobson and Light, 2003;) and on LASA Jacobson et al, 2007;Suszcynsky and Heavner, 2003;Wiens et al, 2008). Recently it has been shown that the VHF pulse in the TIPP associated with NBEs is neither polarized nor coherent (Jacobson et al, 2011).…”
Section: A R Jacobson and T E L Light: Revisiting "Narrow Bipolamentioning
confidence: 99%
“…The 222-record study (Light et al, 2001a) served as an instructive case study, but the relatively small data set did not permit compelling statistical results regarding the occurrence of the unusual, very intense unpolarized TIPPs that are associated with NBEs (Jacobson and Light, 2003). The present paper takes the same approach of using optically controlled VHF recordings, so that the VHF features which are collected are not biased by their own need to trigger at some threshold.…”
Section: Is the Accompanying Optical Emission?mentioning
confidence: 99%
“…While lacking a continental-scale operational capability such as that of the National Lightning Detection Network (Cummins et al, 1998;Cummins and Murphy, 2009), LASA provided close-in location of a lightning-prone area and, most importantly, recorded, stored and archived detailed lighting-stroke radiated waveforms in the frequency range ∼ 1-300 kHz. These waveforms, when compared with coincident FORTE TATR recordings of VHF emissions from the same event, allowed extensive study of the association of strong TIPPs with NBE strokes (Jacobson, 2003a, b;Jacobson and Light, 2003;Smith et al, 1999b). Later (2005 et seq) LASA also was deployed at several stations in the US Great Plains (Wiens et al, 2008).…”
Section: Los Alamos Sferic Array (Lasa)mentioning
confidence: 99%
“…Our technical approach is based on the recording of narrow LF signals from the unique lightning stroke known as an "NBE", or Narrow Bipolar Event (Jacobson, 2003;Jacobson and Light, 2003;Smith et al, 1999). NBEs are received by LF recorders of the transient vertical electric field at ground level, e.g.…”
Section: General Approachmentioning
confidence: 99%